Enhanced piezoelectric performance of electrospun PVDF nanofibers by regulating the solvent systems - Bilal Zaarour; Wanjun Liu (Journal of Engineered Fibers and Fabrics, 2022)
In recreant years, the attention of researchers has been focused on enhancing the electrical outputs of energy harvesting devices. This study reports the generation and characterization of electrospun polyvinylidene fluoride (PVDF) nanofiber webs obtained from different solvents (Acetone (ACE), ACE: N, N-dimethylformamide (DMF) /3:1, ACE: DMF/1:1, ACE: DMF/1:3, and DMF). These electrospun webs will be used as active layers for piezoelectric nanogenerator (PENG). We found that fibers electrospun using DMF have the highest phase content (F(β)), while fibers electrospun using ACE have the lowest one. Furthermore, the results show that PENG based on fiber web electrospun using DMF has the highest electrical outputs, whereas, the lowest electrical outputs were for PENG based on fiber web electrospun using ACE. We believe this work can serve as a good reference for investigating the effect of solvent systems on diameters of fibers, crystalline phases, and piezoelectric properties.